Wood ducks and hooded mergansers as interspecific brood parasites: An evaluation of parasitic egg survival - Dylan L. Bakner; Kevin M. Ringelman; Larry A. Reynolds; Richard M. Kaminski; Scott E. Stephens; J. Brian Davis (Ecology and Evolution)
Abstract Conspecific and interspecific brood parasitism are alternate reproductive strategies more pervasive in waterfowl than in any other group of birds. While previous research has measured costs incurred by nest hosts incubating parasitized clutches, few studies have focused on the relative success of parasites. Here, we evaluated the success of wood duck (Aix sponsa) and hooded merganser (Lophodytes cucullatus) eggs laid parasitically in Louisiana and Mississippi. We monitored nest boxes, assigned eggs in each nest as host or parasitic, and determined the number of eggs that hatched and failed. Across all study areas (1994–1999 and 2020–2023), we monitored 1750 wood duck and 377 hooded merganser nests; ~13% of wood duck and ~24% of hooded merganser nests were interspecifically parasitized. We modeled egg survival of 2925 host and 691 parasitic eggs from 197 successful nests (≥1 hatched egg, regardless of species). Wood duck eggs laid in hooded merganser nests had lower survival [0.293, CI = 95% credible intervals (after, CI) = 0.176, 0.439] than hooded merganser eggs (0.762, CI = 0.704, 0.810) laid in wood duck nests. Clutch size negatively influenced parasitic wood duck egg survival (β = −.24, CI = −0.39, −0.10) but had a slight positive influence on parasitic hooded merganser eggs (β = .08, CI = 0.04, 0.12). Our results revealed that hooded merganser eggs experience higher success when laid parasitically in wood duck nests, whereas wood duck eggs experience lower success when laid parasitically in hooded merganser nests. Our results reveal new complexity in waterfowl interspecific brood parasitism, where the success of parasitic eggs is species‐, host‐, and context‐specific.